2020
DOI: 10.1038/s41598-020-78443-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of hilD in a Salmonella Derby lineage linked to swine adaptation and reduced risk to human health

Abstract: Salmonella enterica variants exhibit diverse host adaptation, outcome of infection, and associated risk to food safety. Analysis of the distribution of Salmonella enterica serovar Derby (S. Derby) subtypes in human and swine identified isolates with a distinct PFGE profile that were significantly under-represented in human infections, consistent with further host adaptation to swine. Here we show that isolates with this PFGE profile form a distinct phylogenetic sub-clade within S. Derby and exhibit a profound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…1A ). This hilC stop and sipA stop -carrying lineage included the 15 isolates carrying also the loss-of-function mutation in hilD previously characterized ( 5 ). The logistic regression performed on the occurrence of the genomes carrying sipA stop and hilC stop in the ST40 population from swine as a function of time (considering also the continent of isolation) showed a significant increase of the fraction of mutation-carrying genomes over time, both in Europe and North America ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A ). This hilC stop and sipA stop -carrying lineage included the 15 isolates carrying also the loss-of-function mutation in hilD previously characterized ( 5 ). The logistic regression performed on the occurrence of the genomes carrying sipA stop and hilC stop in the ST40 population from swine as a function of time (considering also the continent of isolation) showed a significant increase of the fraction of mutation-carrying genomes over time, both in Europe and North America ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we identified a specialized case of host adaptation to swine by a specific S . Derby lineage, featuring even further decreased pathogenicity to humans while maintaining high prevalence in pigs ( 5 ). We found that the lineage carries a single loss-of-function mutation in hilD , encoding the master activator of Salmonella Pathogenicity Island 1 (SPI-1) ( 6 ), and demonstrated that the hilD mutation was responsible for impaired interaction with human cells much more than with swine cells, potentially explaining the negligible presence of this lineage in humans despite its circulation in swine.…”
Section: Introductionmentioning
confidence: 99%
“…The strains were selected in order to represent the phenotype diversity covered by the protocol. In particular, these strains were chosen because their behavior inside epithelial cells was already known to differ in terms of invasion or replication 9 ; therefore, they were valuable controls to test whether the protocol allowed to quantitatively distinguish differences in intracellular Salmonella phenotypes. In particular, S. Tm and S. Derby wt were included because we had previously demonstrated that S. Tm has higher invasion and intracellular replication efficiency than S. Derby wt 9 while S. Derby ΔsipA was added as a hyper-replication impaired strain since the virulence effector SipA plays a crucial role in the onset of hyper-replication 10 , 11 .…”
Section: Infection Of Epithelial Cells With Salmonella Strainsmentioning
confidence: 99%
“…The target of selection is the transcriptional regulation of virulence expression via HilD 12 . Such hilD mutants have been isolated from patients 25 and swine 26 , and are under niche-specific positive selection according to comparative genomic analyses of more than 100 000 natural isolates of Salmonella enterica 27 . Therefore, division of labour alone cannot explain the maintenance of cooperative virulence in S .Tm and much less its emergence.…”
Section: Main Textmentioning
confidence: 99%